(‐)‐Epicatechin and the Colonic 2, 3‐Dihydroxybenzoic Acid Metabolite Regulate Glucose Uptake, Glucose Production, and Improve Insulin Signaling in Renal NRK‐52E Cells. Issue 4 (12th January 2018) - Álvarez‐Cilleros, David; Martín, María Ángeles; Ramos, Sonia
Abstract : Scope: (‐)‐Epicatechin (EC) and main colonic phenolic acids derived from flavonoid intake, such as 2, 3‐dihydroxybenzoic acid (DHBA), 3, 4‐dihydroxyphenylacetic acid (DHPAA), 3‐hydroxyphenylpropionic acid (HPPA), and vanillic acid (VA), have been suggested to exert beneficial effects in diabetes, although the mechanism for their actions remains unknown. In this study, the modulation of glucose homeostasis and insulin signaling by the mentioned compounds on renal proximal tubular NRK‐52E cells is investigated. Methods and results: Levels of the glucose transporters SGLT‐2 and GLUT‐2, as well as glucose uptake, glucose production, and key proteins of the insulin pathways, namely insulin receptor (IR), insulin receptor substrate‐1 (IRS‐1), and PI3K/AKT pathway are analyzed. EC (5‐20 μm ) and DHBA (20 μm ) reduced both renal glucose uptake and production. Interestingly, EC and DHBA did not modify the levels of SGLT‐2 and GLUT‐2, and modulated the expression of phosphoenolpyruvate carboxykinase via AKT leading to a diminished glucose production. EC and DHBA also enhanced the tyrosine phosphorylation and total IR and IRS‐1 levels, and activated the PI3K/AKT pathway in NRK‐52E cells. Conclusion: EC and DHBA regulate the renal glucose homeostasis by modulating both glucose uptake and production, and strengthen the insulin signaling by activating key proteins of that pathway in NRK‐52E cells. Abstract : (‐)‐Epicatechin (EC) and 2, 3‐dihydroxybenzoic acid (DHBA) regulate glucose uptake and strengthen the insulin signaling pathway, as they enhance tyrosine phosphorylation and total levels of IR and IRS‐1, and activate the PI3K/AKT pathway. EC and DHBA modulate the renal gluconeogenesis and PEPCK expression via Anti‐protein kinase B (AKT).